The human face of the urban environment : Proceedings of the second annual World Bank Conference on Environmentally Sustainable Development held at the National Academy of Sciences and the World Bank, Washington, D.C. September 19-21, 1994 - Serageldin, Ismail; Cohen, Michael A.; Sivaramakrishnan, K. C.; World Bank. (Washington, D.C. : World Bank, 1995)
A Report to the Development Community on the Second Annual Conference on Environmentally Sustainable Development Sponsored by the World Bank and Held at the National Academy of Sciences and the World Bank, Washington, D.C., September 19-23, 1994
"Sponsored by The World Bank."
Includes bibliographical references.
oif 09/08/16, ijb 09/04/2019
Loans
Keywords: Pollution; Sustainable urban development; Human ecology